PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV MI AL-WASLIAH SUNGAI MAJO KECAMATAN KUBU KABUPATEN ROKAN HILIR - Zinaida ' '; Zariul Antosa Zariul Antosa; Lazim N ' ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study due to the lowlearning outcomes before PTK IPS studentswith an average grade of 61.8. While the value of minimum completeness criteria(KKM) IPS 65. This research is a classroom action research (CAR). Aiming toimprove the learning outcomes of the fourth grade students of IPS Al-Mi WasliahMajo Rokan Hilir River. Formulation of the problem: Is the application oflearning models kooperati type of make a match can improve learning outcomesIPS grade IV Al-Mi Wasliah Majo Rokan Hilir River. Student learning outcomesbefore the study was 61.8 with a class action less category, while after the actionresearch in the first cycle increased to 71.75 with enough categories and thesecond cycle increased by 75 with either category. Comparison of improvingstudent learning outcomes before action research with action research after thefirst cycle, while there was an increase of 9.95 from the first cycle to the secondcycle there was an increase of 3.25 while kesiklus the basis of scores of 9.95 andan increase of kesiklus two basic score increased by 13.2. Activity teachers havean average of one cycle is 62.49%. While in the second cycle was 79.16%.Activities undertaken while students have an average of one cycle is 66.66% andthe average activity of students in cycle two is 77.08%. These results prove thatthe implementation of cooperative learning model type of make a match canimprove learning outcomes IPS grade IV Al-Mi Wasliah Majo River Rokan Hilir..Keywords: Cooperative Type Make a Match, IPS Learning Outcomes